Transfer laminate, method for producing transfer laminate, method for producing electrode for lithium secondary battery, and lithium secondary battery

By adjusting the temperature of the substrate layer to adjust the oxygen ratio of the lithium metal layer, a suitable transfer laminate is formed, which solves the problem of difficult and side reactions in the transfer-type prelithiation process, and achieves a more efficient lithium metal transfer and prelithiation process.

CN119547220APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053208.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-15
Filing Date
2023-12-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the transfer-type prelithiation process, it is difficult to transfer lithium metal safely and easily, resulting in the failure of lithium to effectively transfer from the transfer laminate, or the lithium metal reacts immediately with the negative electrode active material after transfer, resulting in the breaking of the surface particles of the negative electrode active material layer.

Method used

By adjusting the temperature of the substrate layer, the ratio of lithium element to oxygen element in the surface and specific areas of the lithium metal layer is adjusted to form a suitable transfer laminate, thereby achieving easy transfer of the lithium metal layer.

Benefits of technology

By adjusting the oxygen ratio of the lithium metal layer, the transferability and reactivity of the lithium metal layer when transferred to the electrode is ensured, which solves the problem of difficult transfer of lithium metal and side reactions, and improves the productivity and transferability of the prelithiation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547220A_ABST
    Figure CN119547220A_ABST
Patent Text Reader

Abstract

The present application relates to a transfer laminate, a method for manufacturing a transfer laminate, a method for manufacturing an electrode for a lithium secondary battery, and a lithium secondary battery, including a pre-lithiation process for easily transferring a lithium metal layer by controlling a ratio of lithium element to oxygen element in a surface and a specific region of the lithium metal layer by controlling a temperature of a base material layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0175738 filed in the Korean Intellectual Property Office on December 15, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a transfer laminate, a method for producing a transfer laminate, a method for producing an electrode for a lithium secondary battery, and a lithium secondary battery. [Background Technology]

[0003] Due to the rapid increase in the use of fossil fuels, the demand for the use of alternative energy or clean energy is increasing, and as one of these areas, the most active research area is the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries are representative examples of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to be gradually expanded.

[0005] With the development of technology and the increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for manufacturing high-density electrodes with higher energy density per unit volume are being actively studied.

[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles with high discharge capacity can be used as the negative electrode active material.

[0007] Generally, carbon materials such as graphite are used as negative electrodes for lithium secondary batteries, but the theoretical capacity density of carbon is 372 mAh / g (833 mAh / cm 3 ). Therefore, in order to improve the energy density of the negative electrode, silicon (Si), tin (Sn) and their oxides and alloys alloyed with lithium are considered as negative electrode materials. Among them, silicon-based materials have attracted attention due to their low cost and high capacity (4200mAh / g).

[0008] However, when using silicon-based negative electrode active materials, the problem of large initial irreversible capacity will arise. In the charging and discharging reactions of lithium secondary batteries, the lithium released from the positive electrode during charging is embedded in the negative electrode, and is deintercalated from the negative electrode and returned to the positive electrode during discharge. In the case of silicon-based negative electrode active materials, the volume change and surface side reactions are serious, so that a large amount of lithium embedded in the negative electrode during initial charging cannot return to the positive electrode again, so the initial irreversible capacity increases. When the initial irreversible capacity increases, the problem of rapid reduction in battery capacity and cycle will occur.

[0009] In order to solve the above problems, a method for pre-lithiation of a silicon negative electrode containing a silicon-based negative electrode active material is known. As a pre-lithiation method, known methods include a method for manufacturing an electrode after lithiation by a physical and chemical method such as electrolytic plating, lithium metal transfer and lithium metal deposition, a method for electrochemically pre-lithiating the negative electrode, and the like.

[0010] In order to utilize the existing electrochemical method, a wet process should be performed in the electrolyte, which has the risk of fire, explosion, etc., so it is necessary to control the inert environment. That is, when creating the environment, it is difficult to control conditions such as moisture control using an inert gas in the room where the electrochemical method is performed. In addition, in order to uniformly control the initial irreversible capacity, the electrochemical method should be used to slow down the speed of pre-lithiation as much as possible, so there is a problem of increased production cost when applying the electrochemical method.

[0011] In addition, in the lithium metal transfer process which is a different method, it is difficult to transfer lithium metal safely and easily, lithium is not transferred from the transfer layer stack, or even if lithium metal is transferred, the more reactive lithium metal immediately starts to react with the negative electrode active material, thereby causing problems such as particle breakage on the surface of the negative electrode active material layer.

[0012] In particular, in the transfer type pre-lithiation process, it is very important to ensure the transferability of the lithium metal layer, and only by ensuring the transferability can it be applied to mass production. Currently, research is underway to easily transfer the lithium metal layer from the transfer layer stack, but a safer and faster method for transferring the lithium metal layer has not yet been found.

[0013] Therefore, it is necessary to develop a transfer layer stack that enables lithium to be pre-lithiated more safely and efficiently in the electrode active material layer in a uniform manner during electrode pre-lithiation.

[0014] Prior art literature

[0015] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 [Summary of the invention]

[0016] [Technical issues]

[0017] In the transfer type pre-lithiation process, a technology that can easily transfer the lithium metal layer to the electrode active material layer is necessary. Therefore, methods such as including a release layer or controlling adhesion have been studied, but none of them can clearly solve the above problem. In the present application, it is found through research that when the temperature of the substrate layer is adjusted during the formation of the lithium metal layer on the substrate layer, the ratio of lithium element to oxygen element on the surface and specific area of ​​the lithium metal layer can be adjusted, and when the ratio is adjusted, the lithium metal layer can be easily transferred.

[0018] Therefore, the present application relates to a transfer laminate, a method for producing a transfer laminate, a method for producing an electrode for a lithium secondary battery, and a lithium secondary battery.

[0019] [Technical solution]

[0020] An exemplary embodiment of the present specification provides a transfer laminate including: a substrate layer; and a lithium metal layer laminated on one surface or both surfaces of the substrate layer, wherein the thickness of the lithium metal layer is 1 μm or more and 20 μm or less, and a first region including a thickness of 1 nm or more and 500 nm or less based on a surface of the lithium metal layer opposite to a surface facing the substrate layer satisfies the following Formula 1:

[0021] [Formula 1]

[0022] X / Y×100(%)≤95

[0023] In the above formula 1,

[0024] X represents the oxygen element ratio in atomic % based on the element content in the first region as 100, and

[0025] Y indicates the lithium element ratio in atomic % based on 100 of the element content in the first region.

[0026] Another exemplary embodiment provides a method for manufacturing a transfer laminate, comprising: preparing a substrate layer; and forming a lithium metal layer by heating and depositing a lithium source on a surface of the substrate layer, wherein the surface temperature of the substrate layer in the step of forming the lithium metal layer is below 90°C.

[0027] Another exemplary embodiment provides a method for manufacturing an electrode for a lithium secondary battery, the method comprising: forming an electrode collector layer and an electrode active material layer on one surface or both surfaces of the electrode collector layer; and transferring a lithium metal layer to the electrode active material layer, wherein the transfer of the lithium metal layer comprises preparing a transfer layer stack of the present application, laminating the transfer layer stack onto the electrode active material layer so that a surface of the lithium metal layer opposite to a surface facing the substrate layer contacts a surface of the electrode active material layer opposite to a surface in contact with the electrode collector layer, and removing the substrate layer.

[0028] Finally, a lithium secondary battery is provided, which includes: a positive electrode for a lithium secondary battery; a negative electrode for a lithium secondary battery; a separator arranged between the positive electrode and the negative electrode; and an electrolyte, wherein at least one of the positive electrode for the lithium secondary battery and the negative electrode for the lithium secondary battery is an electrode for a lithium secondary battery manufactured by the above method.

[0029] [Beneficial Effects]

[0030] The transfer laminate of the exemplary embodiment of the present invention is a transfer laminate for a transfer type pre-lithiation process. In particular, the transfer laminate includes a lithium metal layer formed on a substrate layer by heating and depositing a lithium source. In this case, the surface temperature of the substrate layer is adjusted to 90° C. or less in the step of forming the lithium metal layer.

[0031] According to the features of the above manufacturing method, the transfer laminate of the present application satisfies the range of the above formula 1 in the first region including a thickness of 1 nm or more and 500 nm or less based on the surface of the lithium metal layer opposite to the surface facing the substrate layer.

[0032] In the transfer laminate, the composition near the surface of the lithium metal layer satisfies the range of the above formula 1, so by adjusting the oxygen ratio on the surface of the lithium metal layer, the transferability can be ensured when the lithium metal layer is subsequently transferred to the electrode. That is, the surface of the lithium metal layer eventually contacts the surface of the transfer object to which the lithium metal layer is transferred. In this case, by adjusting the oxygen ratio on the surface, the reactivity problem with the transfer object and the transfer force during the transfer process can be adjusted, thereby ensuring productivity in R2R type pre-lithiation and improving transferability.

[0033] That is, the transfer laminate of the present application has an adjusted composition of the lithium metal layer, thereby improving the lithium transferability during the pre-lithiation process, thereby suppressing the generation of byproducts during the pre-lithiation process. [Drawings]

[0034] Figure 1 A transfer laminate according to an exemplary embodiment of the present application is shown.

[0035] Figure 2 A process of transferring lithium metal to an electrode for a lithium secondary battery according to an exemplary embodiment of the present application is shown.

[0036] Figure 3 A stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application is shown.

[0037] Figure 4 The XPS analysis results of the transferred laminate of Example 1 of the present application are shown.

[0038] Figure 5 The XPS analysis results of the transferred laminate of Example 2 of the present application are shown.

[0039] Figure 6 The XPS analysis results of the transferred laminate of Example 3 of the present application are shown.

[0040] Figure 7 The XPS analysis results of the transferred laminate of Comparative Example 1 of the present application are shown.

[0041] Figure 8 The transfer force evaluation results of the transfer laminate of Comparative Example 1 of the present application are shown.

[0042] Fig. 9 The transfer force evaluation results of the transfer laminate of Example 3 of the present application are shown.

[0043] <Description of Reference Numerals>

[0044] 10: Base material layer

[0045] 20: Lithium metal layer

[0046] 30: Electrode active material layer

[0047] 35: Release layer

[0048] 40: Electrode collector layer

[0049] 50: Diaphragm

[0050] 60: Electrode collector layer

[0051] 70: Electrode active material layer

[0052] 100: Transfer laminate

[0053] 200: Electrodes for lithium secondary batteries

[0054] 300: Electrodes for lithium secondary batteries

[0055] A1: First Area

[0056] A2: Second Area [Specific implementation method]

[0057] Before describing the present invention, some terms are first defined.

[0058] When a part of the present specification “includes,” “contains,” or “has” an element, unless otherwise specifically stated, this does not mean that other elements are excluded but means that other elements may also be included.

[0059] In this specification, "p to q" means a range of "p or more and q or less".

[0060] In this specification, the "specific surface area" is measured by the BET method, specifically, it is calculated based on the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II obtained from BEL Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.

[0061] In this specification, "Dn" represents the average particle size, which refers to the particle size at the n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at the 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at the 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at the 10% point in the cumulative distribution of the number of particles according to the particle size. At the same time, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), wherein when the laser beam passes through the particles, the difference in the diffraction pattern generated according to the particle size is measured, and then the particle size distribution is calculated.

[0062] In the present specification, the description "a polymer contains a certain monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, this should be understood as the same as the polymer containing the monomer as a monomer unit.

[0063] In this specification, it is to be understood that the term "polymer" is used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".

[0064] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) while using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard substances. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.

[0065] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0066] An exemplary embodiment of the present specification provides a transfer laminate including: a substrate layer; and a lithium metal layer laminated on one surface or both surfaces of the substrate layer, wherein the thickness of the lithium metal layer is 1 μm or more and 20 μm or less, and a first region including a thickness of 1 nm or more and 500 nm or less based on a surface of the lithium metal layer opposite to a surface facing the substrate layer satisfies the following Formula 1:

[0067] [Formula 1]

[0068] X / Y×100(%)≤95

[0069] In the above formula 1,

[0070] X represents the oxygen element ratio in atomic % based on the element content in the first region as 100, and

[0071] Y indicates the lithium element ratio in atomic % based on 100 of the element content in the first region.

[0072] In the transfer laminate of the present invention, the composition near the surface of the lithium metal layer satisfies the range of the above formula 1, so by adjusting the oxygen ratio on the surface of the lithium metal layer, the transferability can be ensured when the lithium metal layer is subsequently transferred to the electrode. That is, the surface of the lithium metal layer eventually contacts the surface of the transfer object to which the lithium metal layer is transferred. In this case, by adjusting the oxygen ratio on the surface, the reactivity problem with the transfer object and the transfer force during the transfer process can be adjusted, thereby ensuring productivity in R2R type pre-lithiation and improving transferability.

[0073] In an exemplary embodiment of the present application, the substrate layer can be used without restriction as long as it has the characteristics of being able to withstand the process conditions such as the high temperature in the step of depositing the lithium metal layer and prevent the reverse peeling problem of the lithium metal layer being transferred to the substrate layer during the winding process of the transferred deposited lithium metal.

[0074] Specifically, in an exemplary embodiment of the present application, the substrate layer may be one or more selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), polymethyl methacrylate (PMMA), polypropylene, polyethylene, and polycarbonate.

[0075] In an exemplary embodiment of the present application, the thickness of the base material layer may be 1 μm or more and 300 μm or less, and may satisfy the range of 5 μm or more and 200 μm or less or 10 μm or more and 100 μm or less.

[0076] In an exemplary embodiment of the present application, the thickness of the lithium metal layer may be 1 μm or more and 50 μm or less, and may satisfy the range of 3 μm or more and 25 μm or less.

[0077] When the thickness of the substrate layer satisfies the above range, the transfer of the lithium metal layer to the electrode active material layer can be carried out effectively. In particular, when the substrate layer has the above range, heat dissipation can be effectively carried out, thereby preventing the problem of by-product generation during reverse transfer and pre-lithiation.

[0078] In an exemplary embodiment of the present application, a release layer is also included on the surface of the substrate layer of the transfer laminate in contact with the lithium metal layer to improve the stripping property of the lithium metal layer, ensure the transferability to the electrode active material layer, and serve as a protective layer after the lithium metal layer is transferred.

[0079] That is, the substrate layer may have a release layer formed on at least one surface, or may have release layers formed on both surfaces. The release layer prevents the reverse peeling problem of the lithium metal layer being transferred to the substrate layer during the winding process of transferring the deposited lithium metal layer to the electrode, and also facilitates the separation of the substrate layer after the lithium metal is transferred to the electrode active material layer.

[0080] In an exemplary embodiment of the present application, the thickness of the release layer may be 1 nm or more and 1 μm or less.

[0081] In another exemplary embodiment, the thickness of the release layer may satisfy the range of 1 nm or more and 1 μm or less, preferably 100 nm or more and 1 μm or less, and more preferably 500 nm or more and 1 μm or less.

[0082] The release layer satisfies the above thickness range and satisfies a specific adhesion range. The release layer has the above thickness range, so that the adhesion range with the upper part of the pre-lithiation electrode after pre-lithiation can be adjusted to the lower limit of a certain range, thereby preventing side reactions between the release layer and the electrode active material layer.

[0083] The release layer may include one or more selected from the group consisting of silicon-modified polyester in which silicon chains are grafted to a polyester main chain, acrylic resin, Si, melamine, and fluorine.

[0084] In an exemplary embodiment of the present application, the release layer may be formed by a coating method. For example, the coating method may be a method selected from the group consisting of dip coating, spray coating, spin coating, die coating, gravure coating, micro gravure coating, comma coating, and roller coating, but is not limited thereto. That is, various coating methods that can be used to form a coating layer in the art may be used.

[0085] In an exemplary embodiment of the present application, the release layer may include polymethyl methacrylate (PMMA).

[0086] Regarding the type of the release layer, any release layer used in the art may be used without limitation as long as it satisfies its function.

[0087] In an exemplary embodiment of the present application, the thickness of the lithium metal layer may be 1 μm or more and 20 μm or less.

[0088] In another exemplary embodiment, the thickness of the lithium metal layer may be 1 μm or more and 20 μm or less, preferably 2 μm or more and 15 μm or less, and more preferably 3 μm or more and 10 μm or less.

[0089] In an exemplary embodiment of the present application, the first region including a thickness of 1 nm or more and 10 nm or less based on a surface of the lithium metal layer opposite to a surface facing the substrate layer may satisfy Formula 1 above.

[0090] The transfer laminate used in the transfer type pre-lithiation has a lithium metal layer of the above-mentioned thickness range formed on the substrate layer by heating and depositing a lithium source using thermal evaporation. Thereafter, an inert gas is used to stabilize the surface and form a partial deposited film on the top. During the deposition process, oxygen may be mixed into the deposited film. In this case, it is found that in the present application, the ratio of oxygen to lithium on the surface of the lithium metal layer can be adjusted by adjusting the temperature range of the substrate layer during the lithium metal deposition process, and when the ratio is adjusted to the range of the above formula 1, the transfer of the lithium metal layer can effectively occur.

[0091] In an exemplary embodiment of the present application, the above Formula 1 may be X / Y×100(%)≤95, specifically X / Y×100(%)≤90, and more specifically X / Y×100(%)≤89.

[0092] In an exemplary embodiment of the present application, the above Formula 1 may be 50≤X / Y×100(%), specifically 60≤X / Y×100(%), and more specifically 70≤X / Y×100(%).

[0093] Figure 1 The transfer laminate of the exemplary embodiment of the present application is shown. Specifically, it can be confirmed that the lithium metal layer 10 is stacked on the substrate layer 20, which corresponds to a transfer laminate further including a release layer 35 between the substrate layer 20 and the lithium metal layer 10. In particular, the first region A1 includes a thickness of 1 nm or more and 500 nm or less based on the surface of the lithium metal layer opposite to the surface facing the substrate layer, and may refer to a region including 1 nm or more and 500 nm or less based on the surface of the lithium metal layer.

[0094] In an exemplary embodiment of the present application, the first region of the lithium metal layer may be represented as a region according to XPS component analysis (depth profiling). Specifically, the first region of the lithium metal layer may refer to a region at a thickness position of 10 seconds (from the top of the film).

[0095] XPS composition analysis is a method of obtaining a full scan spectrum of the sample as is, and then obtaining a narrow scan spectrum while performing depth profiling. Specifically, using monatomic Ar ions for up to 4000 seconds, the element ratio can be calculated from the narrow scan spectrum.

[0096] In this case, the first region may refer to any region including 1 nm or more and 500 nm or less, and may refer to a region of the surface of 500 nm belonging to the lithium metal layer. In this case, the atomic % of each element is expressed based on 100 atomic % of the element in the first region.

[0097] In an exemplary embodiment of the present application, X may refer to an oxygen element ratio (atomic %) based on the element content in the first region of 100. Specifically, X may satisfy 30 atomic % or more and 41.5 atomic % or less, preferably 32 atomic % or more and 41 atomic % or less, and more preferably 34 atomic % or more and 41 atomic % or less.

[0098] In an exemplary embodiment of the present application, Y may refer to a lithium element ratio (atomic %) based on the element content in the first region of 100. Specifically, Y may satisfy 43 atomic % or more and 60 atomic % or less, preferably 43 atomic % or more and 55 atomic % or less, and more preferably 43 atomic % or more and 50 atomic % or less.

[0099] In the transfer laminate of the present invention, the composition near the surface of the lithium metal layer satisfies the range of the above formula 1, so by adjusting the oxygen ratio on the surface of the lithium metal layer, the transfer property can be ensured when the lithium metal layer is subsequently transferred to the electrode. That is, by adjusting the ratio to the range of the above formula 1, the reactivity problem with the transfer object and the transfer force during the transfer process can be adjusted, so that the productivity is ensured in the R2R type pre-lithiation, and the transfer property can be improved.

[0100] In an exemplary embodiment of the present application, there is provided a transferred laminate, wherein the second region including a thickness of 1500 nm or more and 1800 nm or less based on a surface of the lithium metal layer opposite to the surface facing the substrate layer may satisfy the following Formula 2.

[0101] [Formula 2]

[0102] X1 / Y1×100(%)≤10

[0103] In the above formula 2,

[0104] X1 denotes an oxygen element ratio in atomic % based on the element content of 100 in the second region, and

[0105] Y1 refers to a lithium element ratio in atomic % based on 100 atomic content in the second region.

[0106] Figure 1 The transfer laminate of an exemplary embodiment of the present application is shown, in which the second region can be confirmed. Specifically, the second region A2 is a region based on the surface of the lithium metal layer opposite to the surface facing the substrate layer including a thickness of 1500 nm or more and 1800 nm or less, and can refer to a region based on the surface of the lithium metal layer including a thickness of 1500 nm or more and 1800 nm or less.

[0107] In an exemplary embodiment of the present application, the second region of the lithium metal layer is the region according to the XPS composition analysis as described above. Specifically, the second region of the lithium metal layer may refer to a region at a thickness position of 3000 seconds (from the top of the film).

[0108] That is, the first region and the second region of the present application may refer to regions at a depth of 10 seconds and a depth of 3000 seconds according to XPS composition analysis, which are applied to the thickness of the lithium metal layer and expressed as the thickness based on the surface of the lithium metal layer.

[0109] In an exemplary embodiment of the present application, the above Formula 2 may be X1 / Y1×100(%)≤10, specifically X1 / Y2×100(%)≤7, and more specifically X1 / Y1×100(%)≤6.9.

[0110] In an exemplary embodiment of the present application, the above Formula 2 may be 1≤X1 / Y1×100(%), specifically 2≤X1 / Y1×100(%), and more specifically 4≤X1 / Y1×100(%).

[0111] In an exemplary embodiment of the present application, X1 may refer to an oxygen element ratio (atomic %) based on the element content in the second region of 100. Specifically, X1 may satisfy 1 atomic % or more and 10 atomic % or less, preferably 2 atomic % or more and 7 atomic % or less, and more preferably 3 atomic % or more and 6.5 atomic % or less.

[0112] In an exemplary embodiment of the present application, Y1 may refer to a lithium element ratio (atomic %) based on the element content in the second region of 100. Specifically, Y2 may satisfy 90 atomic % or more and 99 atomic % or less, preferably 92 atomic % or more and 98 atomic % or less, and more preferably 92 atomic % or more and 97 atomic % or less.

[0113] The second region refers to a region that is deeper than the first region from the surface of the lithium metal layer. In this case, the ratio in the second region satisfies the above range, including an appropriate oxygen ratio, so that the subsequent pre-lithiation process does not cause fire and by-product generation problems. In addition, the pre-lithiation amount is adjusted to an appropriate range, including the above ratio of lithium elements, and the desired amount of pre-lithiation is performed.

[0114] In an exemplary embodiment of the present application, there is provided a transfer laminate, wherein the content of the lithium element is 90 wt % or more based on 100 wt % of the metal element content in the lithium metal layer.

[0115] In another exemplary embodiment, the content of the lithium element may be 90 wt % or more, preferably 91 wt % or more, and 99 wt % or less, preferably 95 wt % or less, based on 100 wt % of the metal element content in the lithium metal layer.

[0116] That is, the lithium metal layer of the present application contains the maximum amount of lithium element for pre-lithiation, and adjusts the oxygen ratio within the range of the above formula 1 and formula 2, respectively. By adjusting the oxygen ratio as described above, the transferability during the pre-lithiation process can be improved, thereby solving the problem of reverse transfer, and inhibiting the generation of by-products caused by side reactions during the pre-lithiation process, thereby obtaining an electrode with better performance.

[0117] In an exemplary embodiment of the present application, in addition to the above-mentioned lithium and oxygen elements, the lithium metal layer may further contain other metal impurities.

[0118] In this case, the content of the metal impurities may be 10 parts by weight or less based on 100 parts by weight of the metal element in the lithium metal layer.

[0119] The metal impurities may include carbon (C) elements, nitrogen (N) elements, and the like.

[0120] Hereinafter, the method for producing the transfer laminate of the present invention will be described in detail.

[0121] An exemplary embodiment of the present application provides a method for manufacturing a transfer laminate, which includes: preparing a substrate layer; and forming a lithium metal layer by heating and depositing a lithium source on a surface of the substrate layer, wherein the surface temperature of the substrate layer in the step of forming the lithium metal layer is below 90°C.

[0122] In an exemplary embodiment of the present application, a deposition method of depositing the lithium metal layer onto the substrate layer may be selected from evaporation deposition, chemical vapor deposition (CVD), and physical vapor deposition, but is not limited thereto, and various deposition methods used in the art may be used.

[0123] In the present application, a method for manufacturing a transfer laminate is provided, which further includes forming a surface protection film on the lithium metal layer by using CO 2 gas alone or a mixture of an inert gas and CO 2 gas after forming the lithium metal layer.

[0124] The method for manufacturing a transfer laminate of the present application adjusts the surface temperature of the substrate layer to the above range in the step of depositing the lithium metal layer, thereby manufacturing a lithium metal layer that satisfies the ranges of the above formulas 1 and 2. That is, it was found that in the manufacture of the transfer laminate, if the temperature conditions when depositing the lithium metal layer are changed, the composition of the lithium metal layer can be changed, and when the temperature conditions within the above range are met, a transfer laminate with guaranteed transferability can be manufactured.

[0125] In an exemplary embodiment of the present application, the surface temperature of the substrate layer in the step of forming the lithium metal layer may be 90° C. or lower and 50° C. or higher, preferably 55° C. or higher.

[0126] In an exemplary embodiment of the present application, the lithium metal layer manufactured according to the above manufacturing method may satisfy Formulas 1 and 2 above.

[0127] The description of Formula 1 and Formula 2 is the same as described above.

[0128] An exemplary embodiment provides a method for manufacturing an electrode for a lithium secondary battery, the method comprising: forming an electrode collector layer and an electrode active material layer on one surface or both surfaces of the electrode collector layer; and transferring a lithium metal layer to the electrode active material layer, wherein the transfer of the lithium metal layer comprises preparing the above-mentioned transfer layer stack, laminating the transfer layer stack onto the electrode active material layer so that the surface of the lithium metal layer opposite to the surface facing the substrate layer contacts the surface of the electrode active material layer opposite to the surface in contact with the electrode collector layer, and removing the substrate layer.

[0129] Figure 2 The process of transferring lithium metal to an electrode for a lithium secondary battery according to an exemplary embodiment of the present application is shown. Specifically, it can be seen that a transfer laminate 100 in which a substrate layer 10, a release layer 35, and lithium metal 20 are sequentially laminated is laminated on an electrode for a lithium secondary battery 200 formed by an electrode collector layer 40 and an electrode active material layer 30, and then the substrate layer 10 of the transfer laminate 100 is removed. Therefore, it can be confirmed that the lithium metal layer and the release layer have been transferred to the electrode active material layer.

[0130] Hereinafter, the method for producing the electrode for a lithium secondary battery of the present invention will be described in detail.

[0131] The method for manufacturing an electrode for a lithium secondary battery according to the exemplary embodiment of the present application may include the steps of forming an electrode collector layer and an electrode active material layer on one surface or both surfaces of the electrode collector layer.

[0132] In an exemplary embodiment of the present application, the electrode may be a negative electrode or a positive electrode.

[0133] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided. In this method, the steps of forming an electrode current collector layer and an electrode active material layer on one or both surfaces of the electrode current collector layer include the step of coating an electrode slurry containing an electrode active material layer composition on one or both surfaces of the electrode current collector layer, and the electrode active material layer composition contains one or more selected from the group consisting of an electrode active material, an electrode conductive material, and an electrode binder.

[0134] In this case, a method for prelithiation of an electrode for a lithium secondary battery is provided, where the electrode active material includes a silicon-based active material, and the silicon-based active material includes one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys.

[0135] In an exemplary embodiment of the present application, the electrode can be a negative electrode, and the method for manufacturing a negative electrode for a lithium secondary battery will be described below.

[0136] The method for manufacturing a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application may include forming a negative electrode current collector layer and a negative electrode active material layer on one or both surfaces of the negative electrode current collector layer.

[0137] In an exemplary embodiment of the present application, the thickness of the negative electrode current collector layer is generally 1 μm to 100 μm. There is no specific limitation on the negative electrode current collector layer as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel with surfaces treated with carbon, nickel, titanium, or silver, or an aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector layer may have fine irregularities on its surface to improve the bonding force of the negative electrode active material, and can be used in various forms, such as a film, sheet, foil, net, porous body, foam body, or non-woven fabric body.

[0138] In an exemplary embodiment of the present application, the thickness of the negative electrode current collector layer can be 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer can be 20 μm or more and 500 μm or less.

[0139] However, the thickness can be variously modified according to the type and use of the negative electrode used, and is not limited thereto.

[0140] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided, wherein the step of forming a negative electrode collector layer and a negative electrode active material layer on one surface or both surfaces of the negative electrode collector layer includes coating a negative electrode slurry containing a negative electrode active material layer composition on one surface or both surfaces of the negative electrode collector layer, and the negative electrode active material layer composition contains one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material and a negative electrode binder.

[0141] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.

[0142] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.

[0143] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.

[0144] The solid content of the negative electrode slurry may refer to the content of the negative electrode active material layer composition contained in the negative electrode slurry, and may refer to the content of the negative electrode active material composition based on 100 parts by weight of the negative electrode slurry.

[0145] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate when forming the negative electrode active material layer, so that particle agglomeration of the negative electrode active material layer composition is minimized, thereby effectively forming the negative electrode active material layer.

[0146] In the exemplary embodiment of the present application, the slurry solvent is not limited thereto as long as it can dissolve the negative electrode active material layer composition, but specifically, distilled water may be used.

[0147] The negative electrode according to an exemplary embodiment of the present application may be formed by coating a negative electrode slurry on a negative electrode collector layer and drying the negative electrode slurry.

[0148] Through the drying step, the slurry solvent in the negative electrode slurry can be dried.

[0149] In an exemplary embodiment of the present application, the negative electrode active material layer composition may include one or more selected from the group consisting of a negative electrode active material, a negative electrode conductive material, and a negative electrode binder.

[0150] In an exemplary embodiment of the present application, a silicon-based active material can be used as a negative electrode active material, or a negative electrode including both a silicon-based active material and a carbon-based active material can be used. In this case, a lithium secondary battery having further improved overall performance such as cycle life characteristics can be manufactured.

[0151] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloy.

[0152] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, it may include 70 parts by weight or more of SiO x (x = 0).

[0153] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiO x (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0154] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be specifically used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on 100 parts by weight of the above-mentioned total silicon-based active material, pure Si particles (SiO x (x = 0)) that are not combined with other particles or elements are included within the above range.

[0155] In the charge and discharge reactions of a lithium secondary battery, during charging, lithium released from the positive electrode is embedded in the negative electrode, and during discharging, it is deintercalated from the negative electrode and returns to the positive electrode. In the case of a silicon-based negative electrode active material, volume change and surface side reactions are severe, such that a large amount of lithium embedded in the negative electrode during the initial charging cannot return to the positive electrode again, resulting in an increase in the initial irreversible capacity. When the initial irreversible capacity increases, problems such as rapid reduction of battery capacity and cycles occur.

[0156] In the present invention, to solve the above problems, the negative electrode of the lithium secondary battery is pre-lithiated to solve the initial irreversible capacity problem. Specifically, during the pre-lithiation process, during the lithium transfer process, lithium metal can be easily transferred from the transfer laminate, and the generation of by-products is suppressed, so that the lithium in the negative electrode active material layer can be pre-lithiated uniformly.

[0157] Please note that the average particle size (D50) of the silicon-based active material of the present invention can be 5μm to 10μm, specifically 5.5μm to 8μm, and more specifically 6μm to 7μm. When the average particle size is within the above range, the specific surface area of ​​the particles is within a suitable range, so that the viscosity of the formed negative electrode slurry is within a suitable range. As a result, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the silicon-based active material has a value above the lower limit of the range, due to the composite made of the conductive material and the binder in the negative electrode slurry, the contact area between the silicon particles and the conductive material is excellent, so that the possibility of maintaining the conductive network is increased, thereby improving the capacity retention rate. Please note that when the average particle size satisfies the above range, excessively large silicon particles are excluded, so that the negative electrode surface formed is smooth. Therefore, the phenomenon of uneven current density during charge and discharge can be prevented.

[0158] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET surface area. The BET surface area of ​​the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 / g. The BET surface area is measured in accordance with DIN 66131 (using nitrogen).

[0159] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.

[0160] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0161] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0162] The negative electrode active material layer composition of the present application includes both a conductive material and a binder that can control the volume expansion rate during charge and discharge even if a silicon-based active material having a significantly higher capacity is used within the above range. Therefore, even if the content of the silicon-based active material is within the above range, the negative electrode active material layer composition does not deteriorate the performance of the negative electrode and has excellent output characteristics during charge and discharge.

[0163] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and its sphericity (roundness) is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0164] In the present application, sphericity (roundness) is determined by the following formula 1, wherein A is the area and P is the boundary line.

[0165] [Formula 1]

[0166] 4πA / P 2

[0167] In the prior art, only graphite compounds are generally used as negative electrode active materials. However, in recent years, with the growing demand for high-capacity batteries, attempts to mix and use silicon compounds to increase capacity have also increased. However, the limitation of silicon compounds is that the volume expands rapidly during the charge / discharge process, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery. Therefore, the type of negative electrode conductive material used with silicon active materials is important.

[0168] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.

[0169] In an exemplary embodiment of the present application, the point-shaped conductive material refers to a material that can be used to improve the conductivity of the negative electrode and has conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and preferably includes carbon black in terms of high conductivity and excellent dispersibility.

[0170] In an exemplary embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be 40 m 2 / g or more and 70m 2 / g or less, preferably 45m 2 / g or above and 65m 2 / g or less, more preferably 50m 2 / g or more and 60m 2 / g or less.

[0171] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.

[0172] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material.

[0173] The planar conductive material can improve conductivity by increasing the surface contact between silicon particles in the negative electrode, and can suppress the disconnection of the conductive path due to volume expansion, and is used as a concept including bulk conductive materials or plate conductive materials.

[0174] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0175] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size leads to easy dispersion without excessive increase in the viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.

[0176] In an exemplary embodiment of the present application, there is provided a negative electrode active material layer composition, wherein the planar conductive material has D10 of 0.5 μm to 1.5 μm, D50 of 2.5 μm to 3.5 μm, and D90 of 7.0 μm to 15.0 μm.

[0177] In an exemplary embodiment of the present application, as for the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area or a low specific surface area planar conductive material may be used.

[0178] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material of the present application can be affected to a certain extent on the electrode performance by the dispersion effect, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0179] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 5 m2 / g or above.

[0180] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 5 m 2 / g and above and 500m 2 / g or less, preferably 5m 2 / g and above and 300m 2 / g or less, more preferably 5m 2 / g and above and 300m 2 / g or less.

[0181] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above and 500m 2 / g or less, preferably 80m 2 / g and above and 300m 2 / g or less, more preferably 100m 2 / g and above and 300m 2 / g or less.

[0182] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 5 m 2 / g or more and 40m 2 / g or less, preferably 5m 2 / g or more and 30m 2 / g or less, more preferably 5m 2 / g or more and 25m 2 / g or less.

[0183] Other negative electrode conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a bundle-like or rope-like secondary shape in which a plurality of carbon nanotube units are arranged side by side or entangled in substantially the same direction as the longitudinal axis of the carbon nanotube unit. The carbon nanotube unit comprises a cylindrical graphite sheet having a nanometer-sized diameter and having an sp2 bonding structure. In this case, depending on the winding angle and structure of the graphite sheet, the characteristics of a conductor or a semiconductor may be exhibited. Compared with entangled carbon nanotubes, bundle-type carbon nanotubes may be more evenly dispersed during the negative electrode manufacturing process, and may more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0184] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.

[0185] In another exemplary embodiment, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0186] The negative electrode conductive material of the present application has a completely different structure from the conductive material used for the positive electrode. That is, the negative electrode conductive material of the present application plays a role in maintaining contact between the silicon-based active materials whose volume expansion is very large due to charge and discharge, and the positive electrode conductive material plays a role in providing some conductivity while acting as a buffer during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of structure and function.

[0187] In addition, the negative electrode conductive material of the present application is applied to the silicon-based active material and has a completely different composition from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material simply has particles smaller than the active material, the conductive material has the characteristics of improving the output characteristics and imparting some conductivity, which is completely different from the negative electrode conductive material applied with the silicon-based active material in the present invention in terms of composition and function.

[0188] In an exemplary embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a different structure and function from the carbon-based active material commonly used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material can be artificial graphite or natural graphite, which refers to a material processed into a spherical or dot-like shape for use in order to facilitate the storage and release of lithium ions.

[0189] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be expressed as plate-like graphite. That is, the planar conductive material is a material included to maintain the conductive path in the negative electrode active material layer, and refers to a material that ensures the conductive path in the negative electrode active material layer in a planar shape, rather than playing a role in storing and releasing lithium.

[0190] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material for ensuring a conductive path, rather than playing a role in storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for storing and releasing lithium, and plays a role in storing and releasing all lithium ions transmitted from the positive electrode.

[0191] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0192] That is, in an exemplary embodiment of the present application, the BET specific surface area of ​​artificial graphite or natural graphite as a carbon-based active material may satisfy 0.1 m 2 / g or more and 4.5m 2 In addition, the plate-like graphite as a planar conductive material has a planar shape and a BET specific surface area of ​​5 m 2 / g or above.

[0193] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and hydrogen is replaced by Li, Na or Ca, etc., and may also include various copolymers thereof.

[0194] The binder of the exemplary embodiment of the present application is used to retain the negative electrode active material and the negative electrode conductive material to prevent the distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. When these effects are met, all general negative electrode binders can be applied. Specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.

[0195] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and 5 parts by weight or more or 10 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition.

[0196] In an exemplary embodiment of the present application, the electrode may be a positive electrode, and a method for manufacturing a positive electrode for a lithium secondary battery will be described below. Here, except for the positive electrode, the same description as the pre-lithiation method of the negative electrode for a lithium secondary battery can be applied.

[0197] The method for manufacturing an electrode for a lithium secondary battery according to the exemplary embodiment of the present application may include the step of forming a positive electrode collector layer and a positive electrode active material layer on one surface or both surfaces of the positive electrode collector layer.

[0198] In an exemplary embodiment of the present application, the positive electrode collector layer is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel with carbon, nickel, titanium or silver etc. treated on the surface, etc., can be used. In addition, the thickness of the positive electrode collector layer can generally be 3 μm to 500 μm, and the surface of the positive electrode collector layer can be formed with fine concave-convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam and a non-woven body.

[0199] The thickness of the positive electrode collector layer can be variously changed depending on the type and purpose of the negative electrode used, and is not limited thereto.

[0200] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided, wherein the step of forming a positive electrode collector layer and a positive electrode active material layer on one surface or both surfaces of the positive electrode collector layer includes the step of coating a positive electrode slurry containing a positive electrode active material layer composition on one surface or both surfaces of the positive electrode collector layer, and the positive electrode active material layer composition contains one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material and a positive electrode binder.

[0201] In an exemplary embodiment of the present application, the above description of the negative electrode slurry may be similarly applied to the positive electrode slurry in addition to the positive electrode.

[0202] In an exemplary embodiment of the present application, the positive electrode active material layer composition may include one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material, and a positive electrode binder.

[0203] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided, wherein the electrode active material includes one or more selected from the group consisting of Ni, Co, Mn, LTO, LFP, RuO2, Nb2O5, Mn3O4, Fe2O3 and Co3O4.

[0204] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be: a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide, such as LiFe3O4; a lithium manganese oxide, such as Li 1+c1 Mn 2-c1O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.6); a Ni-type lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which a part of Li in the chemical formula is replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode can be lithium metal.

[0205] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity and does not cause chemical changes in the constituted battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and the like, any one of which or a mixture of two or more thereof can be used.

[0206] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, any one of which or a mixture of two or more thereof may be used.

[0207] In addition, the above description of the negative electrode active material layer composition can be similarly applied to the contents of the positive electrode active material, the positive electrode conductive material, and the positive electrode binder contained in the positive electrode active material layer composition.

[0208] In an exemplary embodiment of the present application, there is provided a method for manufacturing an electrode for a lithium secondary battery, which includes transferring a lithium metal layer to an electrode active material layer.

[0209] Typically, the pre-lithiation process chemically or physically pre-lithiates lithium metal into the electrode, which can be specifically carried out through a lithium metal transfer process, lithium metal powder deposition, an electrochemical process, or a lithium metal deposition process. The pre-lithiation process of the present application may include a lithium metal transfer process.

[0210] The lithium metal transfer process has the characteristic of being able to transfer highly reactive lithium metal more stably to the electrode active material layer. In this case, a process that can easily transfer lithium metal from the transfer laminate to the electrode active material layer is required.

[0211] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided, wherein the step of transferring a lithium metal layer includes preparing the above-mentioned transfer layer stack, laminating the transfer layer stack onto the electrode active material layer so that the surface of the lithium metal layer opposite to the surface facing the substrate layer is in contact with the surface of the electrode active material layer opposite to the surface in contact with the electrode collector layer, and removing the substrate layer.

[0212] In this case, a method for manufacturing an electrode for a lithium secondary battery is provided, wherein the electrode is heated to 200 kgf / cm2 at a temperature of 30°C or less. 2 The lamination was performed under the following pressure.

[0213] After the lamination step, pre-lithiation of the highly reactive lithium metal and electrode active material layers may be performed.

[0214] In an exemplary embodiment of the present application, a method for manufacturing an electrode for a lithium secondary battery is provided, which includes pre-lithiation of an electrode active material layer after removing a substrate layer, wherein, in the pre-lithiation of the electrode active material layer, the electrode active material layer is pre-lithiation within 30 minutes to 24 hours after transferring lithium metal.

[0215] In the transfer process of the lithium metal layer in the prior art, there is a problem that it is difficult to peel off the substrate layer during the pre-lithiation process after laminating the transfer laminate. Therefore, pre-lithiation will be carried out without removing the substrate layer, and the heat generated during the pre-lithiation process is blocked by the substrate layer and cannot be dissipated, resulting in the formation of by-products on the surface during the pre-lithiation of the lithium metal. In the pre-lithiation method of the lithium secondary battery electrode of the present application, by adjusting the lithium metal layer within the range of the above formulas 1 and 2, the substrate layer can be easily peeled off immediately after the lamination transfer laminate, thereby suppressing the generation of by-products during the pre-lithiation process.

[0216] Provided is a method for producing an electrode for a lithium secondary battery, wherein, in pre-lithiation of an electrode active material layer, the electrode active material layer is pre-lithiated under conditions of 25° C. and 1 atm for 30 minutes to 24 hours.

[0217] The pre-lithiation step is a step of setting conditions for diffusion of lithium metal into the electrode active material layer. Whether the pre-lithiation is completed can be determined based on whether the lithium above the electrode active material layer completely disappears.

[0218] An exemplary embodiment of the present application provides a lithium secondary battery, which includes: a positive electrode for a lithium secondary battery; a negative electrode for a lithium secondary battery; a separator arranged between the positive electrode and the negative electrode; and an electrolyte, wherein at least one of the positive electrode for a lithium secondary battery and the negative electrode for a lithium secondary battery is an electrode for a lithium secondary battery manufactured according to the present application.

[0219] In this case, the release layer 35 used in the pre-lithiation process can be removed as described above, so that it does not remain on the electrode, thereby preventing unnecessary resistance increase. That is, the release layer improves the transfer force, can be used to protect lithium metal before pre-lithiation, and can be removed before injecting the electrolyte.

[0220] In an exemplary embodiment of the present application, the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used in the manufacture of a lithium secondary battery, but is not limited thereto.

[0221] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0222] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0223] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, because they have high dielectric constant, can dissociate lithium salts well, therefore can preferably use.When cyclic carbonate is mixed with the straight-chain carbonate (for example dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant with appropriate ratio, can prepare the electrolyte with high conductivity, therefore can more preferably use.

[0224] Lithium salts can be used as the metal salts. Lithium salts are materials that are easily soluble in non-aqueous electrolytes. For example, lithium salts selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、PF6-、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the group consisting of is used as anion of the lithium salt.

[0225] In addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds (such as difluoroethylene carbonate, etc.), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery.

[0226] An exemplary embodiment of the present invention provides a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0227] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes are naturally within the scope of the appended claims herein.

[0228] Example

[0229] <Preparation Example>

[0230] <Preparation of Transfer Laminate>

[0231] For lithium deposition, lithium metal was placed in a crucible of a thermal evaporator, a PET substrate on which lithium was to be deposited was loaded, and then a 10 -6 Then, the lithium metal was evaporated while the crucible was heated, resulting in the deposition of a lithium metal layer at a level of 3 μm to 10 μm (about 6 μm) on the PET substrate.

[0232] After the lithium metal layer is deposited, CO2 gas is injected to form a lithium carbonate layer on the surface. After a certain period of time, the vacuum is vented, and the sample is taken out for surface and depth composition analysis and transfer evaluation using XPS.

[0233] Each transfer laminate was prepared under the temperature conditions shown in Table 1 below.

[0234] [Table 1]

[0235] Surface temperature of the PET film on which lithium was deposited Example 1 50 to 60°C Example 2 50 to 60°C Example 3 70 to 90°C Comparative Example 1 >100℃

[0236] XPS composition analysis (depth profiling)

[0237] For the transfer laminate prepared above, a sample of about 1 cm×1 cm was prepared for XPS component analysis, and the measurement was performed under the conditions of an X-ray spot size of 200 μm and an Ar ion energy of 2 kV. The etching rate was 0.55 nm / sec based on Ta2O5, which was estimated as the thickness of the lithium metal layer and used in the present invention.

[0238] For compositional analysis, full scan spectra were acquired for the as-received samples, followed by narrow scan spectra acquired while depth profiling was performed. Depth profiling was performed for up to 4000 seconds using monatomic Ar ions, and element ratios were calculated from the narrow scan spectra.

[0239] -X-ray source: monochromatic Al Kα (1486.6eV)

[0240] -X-ray spot size: 400μm for original sample analysis, 200μm for depth profiling

[0241] -Sputtering: Ar monatomic (ion energy: 2 kV, current: low, grid width: 1 mm)

[0242] - Etching rate: 0.55nm / sec based on Ta205

[0243] - Operation mode: CAE (Constant Analyzer Energy) mode

[0244] -Full scan: pass energy 200eV, energy step 1eV

[0245] -Narrow scan: Scan mode, pass energy 50eV, energy step 0.1eV

[0246] - Neutralizing gun: Off

[0247] -SF: Al THERMO1, ECF: TPP-2M, BG minus: Shirley 12

[0248] Here, the lithium thickness may vary based on the Ta2O4, but depth profiling determined it to be 3000 sec => 1650 nm and 10 sec => 5.5 nm.

[0249] The XPS component analysis results of the transferred laminate in Table 1 are shown in Table 2 below, and the transfer characteristics were evaluated and shown in Table 2 below. Figures 4 to 6 The analysis results of Examples 1 to 3 by actual XPS analysis are shown. Figure 7 The XPS results of the transferred laminate of Comparative Example 1 are shown.

[0250] [Table 2]

[0251]

[0252] In Table 2, the transfer characteristics are confirmed by placing a transfer laminate on both sides of the electrode in order to transfer the above-mentioned transfer electrode body, applying a load of about 300kgf for rolling, and then removing the lithium metal layer from the PET substrate layer to confirm whether the sample is transferred. In the case of Examples 1 to 3 of the present application, the surface temperature of the substrate layer in the step of forming the lithium metal layer is adjusted to below 90°C. According to the characteristics of the manufacturing method, the transfer laminate of the present application satisfies the range of Formula 1 above in the first region including a thickness of 1nm or more and 500nm or less based on the surface of the lithium metal layer opposite to the surface facing the substrate layer, which can be confirmed by Table 2 above. For reference, in Examples 1 and 2, Formulas 1 and 2 are at similar levels, and the surface temperature of the PET film on which lithium is deposited is in the range of 50°C to 60°C, and the specific temperatures are different, resulting in the results shown in Table 2 above.

[0253] Therefore, it can be confirmed that the transfer laminates of Examples 1 to 3 have a feature of ensuring transferability when transferring to the electrode later by adjusting the oxygen ratio on the surface of the lithium metal layer. That is, the surface of the lithium metal layer finally contacts the surface of the transfer object to which the lithium metal layer is transferred. In this case, it can be confirmed that by adjusting the oxygen ratio on the surface, the reactivity problem with the transfer object and the transfer force during the transfer process can be adjusted, thereby ensuring productivity in R2R type pre-lithiation and improving transferability.

[0254] That is, it can be confirmed that the transfer laminate of the present application adjusts the composition of the lithium metal layer by adjusting the conditions during the manufacturing process, thereby improving the lithium transferability during the pre-lithiation process, thereby suppressing the generation of by-products during the pre-lithiation process.

[0255] In the case of Comparative Example 1, during the preparation of the transfer laminate, the surface temperature of the substrate layer was too high. Specifically, Figure 8 As shown, it can be confirmed that the transfer of the lithium metal layer does not proceed well.

[0256] On the other hand, Fig. 9 As shown in (Example 3), it was confirmed that when the range of Formula 1 of the present invention is satisfied and the range of Formula 2 is also satisfied, the transfer characteristics of the lithium metal layer are very excellent.

[0257] Specifically, Figure 8 and Fig. 9 Shown is a standard for determining the ease of transfer by attaching a Nitto-31B tape to a surface and then checking whether lithium falls off the PET substrate when the tape is peeled off. Figure 8 It shows that lithium does not separate from the substrate even when the tape is attached and peeled off, Fig. 9It is shown that lithium is easily peeled off from the substrate when the tape is attached and peeled off. In other words, it can be confirmed that the examples of the present application have excellent transfer characteristics compared with the comparative examples, while in the case of comparative example 1, the transfer force is low and the result of the transfer evaluation is failure.

Claims

1. A transfer laminate comprising: a substrate layer; and a lithium metal layer laminated on one surface or both surfaces of the substrate layer, in, The thickness of the lithium metal layer is 1 μm or more and 20 μm or less, and Wherein, based on the surface of the lithium metal layer opposite to the surface facing the substrate layer, the first region including a thickness of 1 nm or more and 500 nm or less satisfies the following Formula 1: [Formula 1] X / Y×100(%)≤95 In the above formula 1, X represents the oxygen element ratio in atomic % based on the element content in the first region as 100, and Y indicates the lithium element ratio in atomic % based on 100 of the element content in the first region.

2. The transfer laminate according to claim 1, wherein: Based on the surface of the lithium metal layer opposite to the surface facing the substrate layer, the second region including a thickness of 1500 nm or more and 1800 nm or less satisfies the following Formula 2: [Formula 2] X1 / Y1×100(%)≤10 In the above formula 2, X1 denotes an oxygen element ratio in atomic % based on the element content of 100 in the second region, and Y1 refers to a lithium element ratio in atomic % based on 100 atomic content in the second region.

3. The transfer laminate according to claim 1, wherein: The content of the lithium element is 90 wt % or more based on 100 wt % of the metal element content in the lithium metal layer.

4. The transfer laminate according to claim 1, wherein: The substrate layer includes one or more selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), polymethyl methacrylate (PMMA), polypropylene, polyethylene, and polycarbonate.

5. The transfer laminate according to claim 1, wherein: The base material layer has a thickness of 1 μm or more and 300 μm or less.

6. The transfer laminate according to claim 1, wherein: The transfer laminate further includes a release layer on a surface of the substrate layer in contact with the lithium metal layer.

7. A method for manufacturing a transfer laminate, the method comprising: preparing a substrate layer; as well as forming a lithium metal layer on one surface of the substrate layer by heating and depositing a lithium source; The surface temperature of the substrate layer during the formation of the lithium metal layer is below 90°C.

8. The method of claim 7, further comprising, after forming the lithium metal layer, forming a surface protection film on the lithium metal layer by using CO2 gas alone or a mixture of an inert gas and CO2 gas.

9. The method of claim 7, wherein: The deposition method for depositing the lithium metal layer on the substrate layer includes one or more selected from the group consisting of evaporative deposition, chemical vapor deposition (CVD), and physical vapor deposition.

10. The method of claim 7, wherein: The lithium metal layer satisfies the following formula 1 and formula 2: [Formula 1] X / Y×100(%)≤95 In the above formula 1, X denotes an oxygen element ratio in atomic % based on an element content of 100 in a first region including a thickness of 1 nm or more and 500 nm or less based on a surface of the lithium metal layer opposite to a surface facing the substrate layer, and Y denotes a lithium element ratio in atomic % based on an element content of 100 in a first region including a thickness of 1 nm or more and 500 nm or less based on a surface of the lithium metal layer opposite to the surface facing the substrate layer, [Formula 2] X1 / Y1×100(%)≤10 In the above formula 2, X1 denotes an oxygen element ratio in atomic % based on an element content of 100 in a second region including a thickness of 1500 nm or more and 1800 nm or less based on a surface of the lithium metal layer opposite to the surface facing the substrate layer, and Y1 refers to a lithium element ratio in atomic % based on an element content of 100 in a second region including a thickness of 1500 nm or more and 1800 nm or less, based on a surface of the lithium metal layer opposite to the surface facing the base layer.

11. A method for manufacturing an electrode for a lithium secondary battery, the method comprising: forming an electrode current collector layer and an electrode active material layer on one surface or both surfaces of the electrode current collector layer; as well as transferring the lithium metal layer to the electrode active material layer, Wherein, the transfer of the lithium metal layer includes preparing a transfer layer stack as described in any one of claims 1 to 6, laminating the transfer layer stack onto the electrode active material layer so that the surface of the lithium metal layer opposite to the surface facing the substrate layer contacts the surface of the electrode active material layer opposite to the surface in contact with the electrode collector layer, and removing the substrate layer.

12. The method of claim 11, wherein: At 200kgf / cm2 at a temperature below 30°C 2 The lamination was performed under the following pressure.

13. The method of claim 11, wherein: The step of forming the electrode collector layer and the electrode active material layer on one surface or both surfaces of the electrode collector layer comprises: coating an electrode slurry containing an electrode active material layer composition on one surface or both surfaces of the electrode collector layer, and The electrode active material layer composition comprises one or more selected from the group consisting of an electrode active material, an electrode conductive material and an electrode binder.

14. The method of claim 13, wherein: The electrode active material includes a silicon-based active material, and Wherein, the silicon-based active material includes one or more selected from the group consisting of SiO where x = 0 x , SiO where 0 < x < 2 x , SiC, and Si alloys.

15. The method of claim 13, wherein: The electrode active material includes one or more selected from the group consisting of Ni, Co, Mn, LTO, LFP, RuO2, Nb2O5, Mn3O4, Fe2O3 and Co3O4.

16. A lithium secondary battery comprising: Positive electrode for lithium secondary battery; Negative electrode for lithium secondary battery; A separator disposed between the positive electrode and the negative electrode; and Electrolytes, in, At least one of the positive electrode for a lithium secondary battery and the negative electrode for a lithium secondary battery is an electrode for a lithium secondary battery manufactured by the method according to claim 11 .

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A